NITRIT OKSIDA DAN VOLUME EDEMA OTAK PADA STROK PERDARAHAN DALAM OTAK DENGAN POLIMORFISME G894T (Nitric Oxide and Cerebral Edema Volume in Intracerebral Hemorrhagic Stroke with G894T Polymorphism) - Iskandar Zakaria; Arif Faisal; Sri Sutarni; Ahmad Hamim Sadewa; Imran Imran (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Nitric Oxide (NO) is a vasodilator that regulates vascular smooth muscle tone. Low levels of NO can cause vasoconstriction andhemodynamic disturbances. In stroke the levels of NO are increased. Endothelial nitric oxide synthase gene polymorphism (eNOS) isbelieved to reduce levels of NO in blood. NO levels decreased in stroke patients with G894T polymorphisms of eNOS gene. Mortality rateof hemorrhagic stroke are increased in case with increased peri focal edema volume. The mechanism of the increased of peri focal edemavolume completely unknown yet, suspected genetics factor. This study was conducted to know the correlation between the NO and perifocal edema volume in stroke with eNOS gene G894T polymorphism by determination. The study was conducted by comparing the levelsof NO and edema volume of intra cerebral hemorrhagic stroke of 46 subjects from Neurology department of dr. Zainoel Abidin generalhospital in Banda Aceh from September 2014 through January 2015 with comparison to ischemic stroke patients the same amount.NO levels checked with Cayman Systems kit following the protocol Griess. G894T polymorphism was determined by PCR-RFLP method.The volume of edema was measured with semi-automatic CT volumetry. Chi Square test was used for comparison of two variables andSpearman correlation test to assess the relationship between the NO and perifocal edema volume. The result is significant, if p valuewas <0.05. The results of these study were levels of NO decreases if there were polymorphism (p=0.001). Peri focal edema volume wasincreased if there were G894T polymorphism (p=0.038). The correlation between low levels of NO and increase of edema volume wasobtained p=0.040 and R=0.304. The researchers concluded that in intra cerebral hemorrhagic stroke the level of NO were decreasedand peri focal edema volume increased if there was G894T polymorphism of eNOS gene. There was a less correlation between low levelsof NO and peri focal edema volume.